Monolith substrate and exhaust gas purification catalyst comprising monolith substrate
A monolith substrate with a ceria component and alumina-ceria-zirconia composite oxide improves low-temperature exhaust gas purification by enhancing oxygen storage capacity and heat resistance, ensuring effective gas contact and rapid oxygen exchange.
Patent Information
- Application Number
- JP2021151953
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-17
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2041-09-17
AI Technical Summary
Existing exhaust gas purification catalysts with honeycomb-shaped monolith substrates exhibit low pressure loss but require improvement in low-temperature activity.
A monolith substrate containing a ceria component with a specific pore volume of 0.03 μm or less and a composition of alumina-ceria-zirconia composite oxide, which enhances oxygen storage capacity and heat resistance, is used to improve low-temperature activity.
The catalyst achieves improved low-temperature exhaust gas purification performance by ensuring a larger contact area with exhaust gases and rapid oxygen absorption and release, maintaining constant oxygen concentration under fluctuating air-fuel ratios.
Smart Images

Figure 0007628922000004 
Figure 0007628922000005 
Figure 0007628922000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a monolith substrate and an exhaust gas purification catalyst comprising the monolith substrate. [Background technology]
[0002] Exhaust gases emitted from internal combustion engines such as automobiles contain harmful gases such as carbon monoxide (CO), nitrogen oxides (NOx), and unburned hydrocarbons (HC). Exhaust gas purification catalysts that decompose such harmful gases are also called three-way catalysts, and are generally made by wash-coating a honeycomb-shaped monolith substrate made of cordierite or the like with a catalyst layer containing catalytically active precious metal particles. Various attempts have been made to improve the performance of such catalysts.
[0003] For example, Patent Document 1 describes a catalyst body in which a catalyst component is directly supported on the surface of a support, the catalyst component being directly supported on at least one of elements and pores in the support, and the support strength between the elements or pores in the support and the catalyst component being greater than 5 eV as determined by a simulation using a density functional theory method.
[0004] Patent Document 2 describes a flow-type exhaust gas purification catalyst in which a catalyst carrier and a catalyst component are supported on a honeycomb substrate, characterized in that at least 90% by weight of the catalyst carrier and the catalyst component are each disposed within the pores of the cell walls of the honeycomb substrate.
[0005] Patent Document 3 describes a ceramic catalyst body in which a main catalyst component and a promoter catalyst component are supported on a ceramic carrier capable of directly supporting the catalyst component on the surface of a substrate ceramic, the ceramic substrate having a structure having a large number of pores, and the main catalyst component and the promoter catalyst component are directly supported on the surface of the substrate ceramic including the inner surfaces of these pores.
[0006] Patent Document 4 describes an exhaust gas purification catalyst in which precious metal particles are supported on a monolith substrate containing ceria-zirconia composite oxide particles and θ-phase alumina particles, with the content of the ceria-zirconia composite oxide particles being 25 wt % or more relative to the total weight. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-236381 A [Patent Document 2] JP 2003-170043 A [Patent Document 3] JP 2004-066069 A [Patent Document 4] JP 2015-085241 A Summary of the Invention [Problem to be solved by the invention]
[0008] Exhaust gas purification catalysts in which precious metal particles (in some cases, the precious metal particles are supported on a carrier) are supported on a honeycomb-shaped monolith substrate, as described in Patent Documents 1 to 4, can maintain low pressure loss, but there is room for improvement in exhaust gas purification performance at low temperatures (also known as "low-temperature activity").
[0009] In view of the above, an object of the present invention is to provide a monolith substrate for an exhaust gas purification catalyst for improving low-temperature activity, and an exhaust gas purification catalyst including the monolith substrate. [Means for solving the problem]
[0010] As a result of examining the above-mentioned problems, the present inventors have found that it is possible to provide a monolith substrate that solves the above-mentioned problems and an exhaust gas purification catalyst that includes the monolith substrate by using a honeycomb-shaped monolith substrate that contains a ceria component and has a specific pore volume of a certain value or more as the monolith substrate, and have thus completed the present invention.
[0011] The gist of the present invention is as follows. (1) A honeycomb-shaped monolith substrate containing a ceria component and having a pore volume of 0.03 μm or less of 0.20 ml / g or more. (2) The monolith substrate according to (1), wherein the content of the ceria component is 6% by weight or more and less than 13% by weight, based on the total weight of the monolith substrate. (3) The monolith substrate according to (1) or (2), which contains an alumina-ceria-zirconia composite oxide as the ceria component. (4) The monolith substrate according to (3), wherein the content of the alumina-ceria-zirconia composite oxide is 40% by weight to 60% by weight based on the total weight of the monolith substrate. (5) The monolith substrate according to any one of (1) to (4), further comprising alumina particles. (6) The monolith substrate according to (5), wherein the content of the alumina particles is 28% by weight to 32% by weight based on the total weight of the monolith substrate. (7) An exhaust gas purification catalyst comprising the monolith substrate according to any one of (1) to (6) above and precious metal particles. Effect of the Invention
[0012] According to the present invention, it is possible to provide a monolith substrate for an exhaust gas purification catalyst for improving low-temperature activity, and an exhaust gas purification catalyst including the monolith substrate. [Brief description of the drawings]
[0013] [Figure 1] 1 is a graph showing the relationship between the ACZ ratio and the volume of pores of 0.03 μm or less in the exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3. [Diagram 2] 1 is a graph showing the relationship between the pore volume of 0.03 μm or less and the low-temperature activity HC-T10 of the exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Preferred embodiments of the present invention will now be described in detail. The monolith substrate of the present invention and the exhaust gas purification catalyst comprising the monolith substrate are not limited to the following embodiments, and can be embodied in various forms including modifications and improvements that can be made by a person skilled in the art within the scope of the present invention.
[0015] The present invention relates to a honeycomb-shaped monolith substrate containing a ceria component and having a pore volume of 0.03 μm or less that is equal to or greater than a certain value, and an exhaust gas purification catalyst comprising the monolith substrate.
[0016] Here, the honeycomb-shaped monolith substrate is, for example, a monolith substrate having a known honeycomb shape (for example, a honeycomb structure, a honeycomb filter, a high-density honeycomb, etc.).
[0017] The size and volume of the honeycomb monolith substrate are not limited and may be any size and volume known in the art.
[0018] The pore volume of the monolith substrate of the present invention having a particle size of 0.03 μm or less is 0.20 ml / g or more, preferably 0.22 ml / g or more. There is no upper limit to the pore volume of the monolith substrate of the present invention having a particle size of 0.03 μm or less.
[0019] Methods for measuring the pore volume of 0.03 μm or less in the monolith substrate of the present invention are known in the art, for example, mercury intrusion porosimeter. Mercury intrusion porosimeter is a method in which pressure is applied to mercury, which has a high surface tension, to force the mercury into pores or gaps in the surface of a solid to be measured, and the pore distribution is determined from the relationship between the applied pressure and the volume of the mercury that has been forced in.
[0020] For example, the pore volume of the monolith substrate of the present invention having a diameter of 0.03 μm or less is measured by mercury intrusion porosimetry in accordance with JISR1655:2003. Specifically, a cube having a side length of about 0.8 cm is cut out from the monolith substrate as a measurement sample, which is then ultrasonically cleaned with ion-exchanged water and thoroughly dried. The pore volume of the measurement sample is then measured by a pore volume measuring device using mercury intrusion porosimetry, for example, an automatic porosimeter Autopore III9405 (manufactured by Micromeritics). The measurement range is the pore volume of pores with a diameter of 0.006 μm to 500 μm, and the pore volume of pores with a diameter of 100 μm to 500 μm is measured at a pressure of 0.1 psia, and the pore volume of pores with a diameter of 0.006 μm to 100 μm is measured at a pressure of 0.25 psia. At this time, the contact angle is set to 130° and the surface tension is set to 485 mN / m. From the obtained pore volume results for pore diameters in the range of 0.006 μm to 500 μm, the pore volume for pores of 0.03 μm or less is calculated.
[0021] When the monolith substrate of the present invention has a pore volume of 0.03 μm or less within the above-mentioned range, the contact area between the exhaust gas and the exhaust gas purification catalyst comprising the monolith substrate can be secured, and the low-temperature activity of the exhaust gas purification catalyst can be improved.
[0022] The monolith substrate of the present invention contains a ceria component.
[0023] The ceria component contained in the monolith substrate of the present invention is a component for ensuring oxygen storage / release capacity (OSC).
[0024] The content of the ceria component is usually 6% by weight or more and less than 13% by weight, and preferably 8% by weight or more and less than 13% by weight, based on the total weight of the monolith substrate.
[0025] When the content of the ceria component falls within the above range, a sufficient OSC can be ensured in the exhaust gas purification catalyst including the monolith substrate.
[0026] The monolith substrate of the present invention preferably contains an alumina-ceria-zirconia composite oxide as the ceria component.
[0027] In internal combustion engines such as automobiles, the air-fuel ratio (A / F), which is the mixture ratio of air and fuel, can vary depending on the driving conditions. For example, when it is desired to improve fuel efficiency and reduce harmful gases, an automobile is operated in an air-fuel ratio with a higher air ratio, i.e., in a lean state, and when a large output is required, such as when starting or accelerating, an air-fuel ratio with a higher fuel ratio, i.e., in a rich state.
[0028] In an internal combustion engine in which the air-fuel ratio fluctuates as described above, the composition of the exhaust gas discharged therefrom may also fluctuate. Therefore, there is a demand for an exhaust gas purification catalyst that can sufficiently purify exhaust gases whose composition may fluctuate.
[0029] When the monolith substrate contains an alumina-ceria-zirconia composite oxide which has a fast oxygen absorption / release rate, particularly compared to a ceria-zirconia composite oxide, the monolith substrate can rapidly absorb and release oxygen to maintain a constant oxygen concentration even under conditions in which the air-fuel ratio fluctuates (A / F transient conditions), particularly under conditions in which the air-fuel ratio fluctuates within a small range, i.e., under conditions in which the change in exhaust gas concentration is small, and therefore an exhaust gas purification catalyst comprising the monolith substrate has a high ability to maintain stoichiometry and can have high exhaust gas purification performance, particularly improved low-temperature activity against HC.
[0030] Furthermore, the alumina-ceria-zirconia composite oxide has high heat resistance. Therefore, by including an alumina-ceria-zirconia composite oxide having high heat resistance, particularly higher heat resistance than a ceria-zirconia composite oxide, in a monolith substrate, the monolith substrate including the alumina-ceria-zirconia composite oxide, and further the exhaust gas purification catalyst including the monolith substrate, can maintain a large pore volume of 0.03 μm or less.
[0031] The alumina-ceria-zirconia composite oxide is composed of alumina-ceria-zirconia composite oxide particles.
[0032] In the alumina-ceria-zirconia composite oxide, ceria and zirconia are dispersed in alumina, and a part of the ceria and zirconia forms a ceria-zirconia solid solution. The structure of the alumina-ceria-zirconia composite oxide can be observed with a transmission electron microscope (TEM) or the like. The fact that the ceria and zirconia form a ceria-zirconia solid solution can be confirmed, for example, by X-ray diffraction (XRD).
[0033] The composition of the alumina-ceria-zirconia composite oxide is usually Ce:Zr=1:5 to 3:1, and usually Al:(Ce+Zr)=1:1 to 1:10, in molar ratio. Furthermore, the alumina-ceria-zirconia composite oxide contains ceria in an amount of usually 15% by weight or more, preferably 20% by weight or more, and further contains ceria in an amount of usually 50% by weight or less, preferably 40% by weight or less. The composition of the alumina-ceria-zirconia composite oxide depends on the composition of the alumina-ceria-zirconia composite oxide used as a material in the production of the monolith substrate.
[0034] By setting the composition of the alumina-ceria-zirconia composite oxide within the above range, it is possible to fully obtain the effects of suppressing particle growth by alumina (improving heat resistance, ensuring specific surface area and pore volume of 0.03 μm or less), ensuring oxygen storage and release performance (OSC) by ceria, and ensuring the stabilizing effect of ceria by zirconia.
[0035] The alumina-ceria-zirconia composite oxide may further contain one or more elements selected from rare earth elements other than cerium. Examples of rare earth elements include scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu). Preferred rare earth elements are Y and La. The content of the rare earth element is usually 1% by weight to 20% by weight in terms of oxide, based on the total weight of the alumina-ceria-zirconia composite oxide.
[0036] When the alumina-ceria-zirconia composite oxide contains a rare earth element, the heat resistance of the alumina-ceria-zirconia composite oxide can be improved, and the OSC can be improved.
[0037] The content of the alumina-ceria-zirconia composite oxide is usually 40% by weight to 60% by weight, preferably 40% by weight to 50% by weight, based on the total weight of the monolith substrate. The content of the alumina-ceria-zirconia composite oxide contained in the monolith substrate of the present invention depends on the amount of the alumina-ceria-zirconia composite oxide added as a material during the production of the monolith substrate.
[0038] By having the content of the alumina-ceria-zirconia composite oxide in the monolith substrate fall within the above range, the monolith substrate can maintain a pore volume of 0.03 μm or less, and can rapidly absorb and release oxygen to keep the oxygen concentration constant, even under conditions in which the air-fuel ratio fluctuates, particularly under conditions in which the air-fuel ratio fluctuates within a small fluctuation range, i.e., under conditions in which the change in exhaust gas concentration is small. Therefore, an exhaust gas purification catalyst comprising the monolith substrate can have a higher ability to maintain the stoichiometry, and can have higher exhaust gas purification performance, in particular improved low-temperature activity against HC.
[0039] The monolith substrate of the present invention may further contain a ceria-zirconia composite oxide as a ceria component.
[0040] The ceria-zirconia composite oxide is composed of ceria-zirconia composite oxide particles.
[0041] When the monolith substrate contains a ceria-zirconia composite oxide, a sufficient OSC can be ensured.
[0042] The ceria-zirconia composite oxide contains ceria in an amount of usually 15% by weight or more, preferably 20% by weight or more, and further contains ceria in an amount of usually 70% by weight or less, preferably 60% by weight or less. The ceria-zirconia composite oxide contains zirconia in an amount of usually 80% by weight or less, preferably 70% by weight or less. Such a ceria-zirconia composite oxide has a small heat capacity, so that it is easy to increase the temperature of the monolith substrate, thereby improving the warm-up performance of the catalyst. The composition of the ceria-zirconia composite oxide contained in the monolith substrate of the present invention depends on the composition of the ceria-zirconia composite oxide as a material when the monolith substrate is manufactured.
[0043] The ceria-zirconia composite oxide may further contain one or more elements selected from rare earth elements other than cerium. Examples of rare earth elements include scandium (Sc), yttrium (Y), lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), ytterbium (Yb), and lutetium (Lu). Preferred rare earth elements are Y and La. The content of the rare earth element, as oxide, is usually 5% by weight to 25% by weight based on the total weight of the ceria-zirconia composite oxide.
[0044] When the ceria-zirconia composite oxide contains a rare earth element, the heat resistance of the ceria-zirconia composite oxide can be improved, and the OSC can be improved.
[0045] The content of the ceria-zirconia composite oxide, if present, is usually 30% by weight or less, preferably 20% by weight or less, based on the total weight of the monolith substrate. The lower limit of the content of the ceria-zirconia composite oxide is not limited, since the monolith substrate of the present invention does not necessarily need to contain the ceria-zirconia composite oxide. The content of the ceria-zirconia composite oxide contained in the monolith substrate of the present invention depends on the amount of the ceria-zirconia composite oxide added as a material during the production of the monolith substrate.
[0046] By setting the content of the ceria-zirconia composite oxide within the above range, the monolith substrate can maintain a pore volume of 0.03 μm or less, while quickly absorbing and releasing oxygen to keep the oxygen concentration constant, even under conditions in which the air-fuel ratio fluctuates, particularly under conditions in which the air-fuel ratio fluctuates within a small fluctuation range, i.e., under conditions in which the change in exhaust gas concentration is small. Therefore, an exhaust gas purification catalyst produced by supporting precious metal particles on a monolith substrate can have a higher ability to maintain the stoichiometry and can have higher exhaust gas purification performance, in particular improved low-temperature activity against HC.
[0047] The monolith substrate of the present invention may further comprise alumina.
[0048] Here, the alumina that can be contained in the monolith substrate of the present invention includes alumina particles.
[0049] When the monolith substrate contains alumina particles, the alumina particles, which have higher heat resistance than an alumina-ceria-zirconia composite oxide, function as a support for precious metals, improving the durability of an exhaust gas purification catalyst comprising the monolith substrate and suppressing a decrease in the pore volume of 0.03 μm or less of the exhaust gas purification catalyst, i.e., making it possible to maintain the pore volume of 0.03 μm or less of the exhaust gas purification catalyst.
[0050] The content of the alumina particles is usually 28% by weight to 32% by weight, and preferably 29% by weight to 31% by weight, based on the total weight of the monolith substrate. The content of the alumina particles contained in the monolith substrate of the present invention depends on the amount of the alumina particles added as a material during the production of the monolith substrate.
[0051] When the content of alumina particles in the monolith substrate is within the above range, as described above, the alumina particles secure a support field for the precious metal, thereby obtaining sufficient durability, and suppressing a decrease in the pore volume of 0.03 μm or less in an exhaust gas purification catalyst comprising the monolith substrate, i.e., making it possible to maintain the pore volume of 0.03 μm or less in the exhaust gas purification catalyst.
[0052] In addition to alumina particles, the alumina may include amorphous alumina and / or fibers derived from an alumina binder and / or alumina fibers that may be added during the manufacture of the monolith substrate.
[0053] When the monolith substrate contains amorphous and / or fibrous alumina, the alumina acts as a binder between oxide particles and / or a reinforcing material for the monolith structure of the monolith substrate, thereby improving the physical stability of the exhaust gas purification catalyst.
[0054] The content of the alumina binder and / or alumina fiber is usually 10% by weight to 35% by weight, preferably 15% by weight to 30% by weight, based on the total weight of the monolith substrate. The content of the alumina particles contained in the monolith substrate of the present invention depends on the amount of the alumina binder and alumina fiber added as materials during the production of the monolith substrate.
[0055] By setting the content of the alumina binder and / or alumina fiber in the monolith substrate within the above range, as described above, sufficient physical stability of the exhaust gas purification catalyst including the monolith substrate can be ensured.
[0056] Therefore, the alumina content in the monolith substrate (including alumina in the alumina-ceria-zirconia composite oxide) is usually 67% by weight or more, and preferably 67% by weight to 80% by weight, based on the total weight of the monolith substrate. The alumina content in the monolith substrate of the present invention depends on the amounts of alumina particles, alumina binder, and alumina fiber added as materials during the production of the monolith substrate.
[0057] By ensuring that the alumina content in the monolith substrate falls within the above range, as described above, sufficient heat resistance and durability of the exhaust gas purification catalyst including the monolith substrate can be ensured, and further, a decrease in the pore volume of 0.03 μm or less can be suppressed.
[0058] The monolith substrate of the present invention can be manufactured by the same procedures as those for conventional cordierite substrates, except that a material containing ceria is used as the material and the pore volume of 0.03 μm or less is adjusted to the above-mentioned range by adjusting the firing temperature, firing time, and the like in the firing conditions.
[0059] For example, the monolith substrate of the present invention can be produced by adding water as a solvent and a binder, such as an alumina binder and / or alumina fiber, to a mixture of alumina-ceria-zirconia composite oxide particles and alumina particles, kneading the mixture, and then molding the mixture using an extruder or the like. After drying using, for example, a microwave dryer, hot air dryer, dielectric dryer, reduced pressure dryer, vacuum dryer, freeze dryer, or the like, the mixture is fired, for example, typically at 900°C to 1200°C for typically 1 hour to 24 hours.
[0060] In the materials used for producing the monolith substrate of the present invention, the alumina-ceria-zirconia composite oxide may be one known in the art, for example, one described in JP-A-10-202102 and JP-A-2001-232199.
[0061] For example, the alumina-ceria-zirconia composite oxide can be prepared by an alkoxide method or a coprecipitation method. By preparing the alumina-ceria-zirconia composite oxide by the alkoxide method or the coprecipitation method, a composite oxide consisting of uniform and fine primary particles can be prepared, and a composite oxide containing a ceria-zirconia solid solution can be easily prepared.
[0062] In the alkoxide method, for example, all metal alkoxides of aluminum, cerium, zirconium, and optionally rare earth elements are mixed, hydrolyzed, and then calcined to prepare an alumina-ceria-zirconia composite oxide. In addition, even if all of aluminum, cerium, zirconium, and optionally rare earth elements are not used as metal alkoxides, as long as at least one of them is used as a metal alkoxide, the remaining metals can be used as a solution such as a nitrate or acetylacetate salt.
[0063] The metal alkoxide may be any of methoxide, ethoxide, butoxygen, etc., and is preferably one having high solubility in the alcohol solvent. Any alcohol may be used as the solvent.
[0064] In the coprecipitation method, for example, water-soluble salts such as nitrates of all metals, aluminum, cerium, zirconium, and optionally rare earth elements, are mixed, co-precipitated as hydroxides with ammonia water, etc., and then calcined to prepare an alumina-ceria-zirconia composite oxide. Also, even if all of aluminum, cerium, zirconium, and optionally rare earth elements are not used as water-soluble salts, as long as at least one of them is used as a water-soluble salt, the remaining metals can be used as solids such as metal powders or oxide powders.
[0065] The alumina-ceria-zirconia composite oxide thus obtained is preferably previously heat-treated, usually at 500° C. to 900° C. By previously heat-treating the alumina-ceria-zirconia composite oxide, excessive crystal growth of the particles can be suppressed, and the decrease in OSC after durability testing can be further suppressed.
[0066] The crystallites of the ceria-zirconia composite oxide in the alumina-ceria-zirconia composite oxide are preferably fine, and the crystallite diameter is usually 30 nm or less, preferably 5 nm to 20 nm. The crystallite diameter of the ceria-zirconia composite oxide can be measured, for example, by the half-width of XRD.
[0067] By setting the crystallite size of the ceria-zirconia composite oxide in the alumina-ceria-zirconia composite oxide within the above range, the effect of ensuring OSC by ceria can be sufficiently obtained.
[0068] The BET specific surface area of alumina-ceria-zirconia composite oxide is usually 50m 2 / g or more, preferably 60m 2 / g~80m2 / g.
[0069] By setting the BET specific surface area of the alumina-ceria-zirconia composite oxide within the above range, the effect of ensuring OSC by ceria can be sufficiently obtained.
[0070] As described above, compared with ceria-zirconia composite oxide, alumina-ceria-zirconia composite oxide is less susceptible to particle (crystal) growth and has high heat resistance even in a high-temperature environment such as the firing temperature of the monolith substrate. Therefore, the particles of the alumina-ceria-zirconia composite oxide in the monolith substrate after production have a particle size equal to or slightly larger than the particle size of the alumina-ceria-zirconia composite oxide particles used as the material of the monolith substrate, even when considering particle (crystal) growth due to firing during the production of the monolith substrate. Therefore, the particles of the alumina-ceria-zirconia composite oxide contained in the monolith substrate of the present invention obtained in this manner have a small particle size, i.e., a large specific surface area, a large pore volume of 0.03 μm or less, and a high OSC even after production.
[0071] In the materials used for producing the monolith substrate of the present invention, the alumina may be in the form of alumina particles, alumina binder, alumina fiber, or the like.
[0072] The alumina particles that can be used are generally commercially available as catalyst supports in the art.
[0073] By using alumina particles as the alumina, the alumina particles, which have higher heat resistance than alumina-ceria-zirconia composite oxide, function as a support for the precious metal, thereby improving the durability of the catalyst.
[0074] The alumina particles include, but are not limited to, α-phase alumina particles, θ-phase alumina particles, δ-phase alumina particles, etc. The alumina particles are preferably θ-phase alumina particles or δ-phase alumina particles. The crystal structure of the alumina particles can be confirmed, for example, by powder X-ray diffraction (XRD).
[0075] Since the alumina particles are generally θ-phase alumina particles or δ-phase alumina particles, which have a high surface area, the surface area can be maintained high even after being incorporated into the monolith substrate of the present invention, and deterioration of the precious metal can be suppressed.
[0076] The BET specific surface area of alumina particles is typically 60m 2 / g~150m 2 / g, preferably 80m 2 / g~120m 2 / g.
[0077] By setting the BET specific surface area of the alumina particles within the above range, the alumina particles can function as a metal supporting field, thereby improving the durability of the catalyst.
[0078] The alumina binder and alumina fibers that can be used are those generally available commercially in the art.
[0079] By using an alumina binder as the alumina, the alumina binder plays a role as a binding agent between oxide particles, and the physical stability of the monolith substrate can be improved. Furthermore, by using an alumina fiber as the alumina, the alumina fiber plays a role as a reinforcing material for the monolith structure of the monolith substrate, and the physical stability of the monolith substrate can be improved.
[0080] Among the materials that can be used to manufacture the monolith substrate of the present invention, the ceria-zirconia composite oxide is a material that has been used as a co-catalyst (oxygen storage material) in conventional exhaust gas purification catalysts, and details thereof are known to those skilled in the art. The ceria-zirconia composite oxide is preferably a solid solution of ceria and zirconia. The ceria-zirconia composite oxide can be prepared by the alkoxide method or the coprecipitation method. In the case of the coprecipitation method, for example, ammonia water is added to an aqueous solution in which a cerium salt (such as cerium nitrate) and a zirconium salt (such as zirconium oxynitrate) are dissolved to generate a coprecipitation, and the obtained precipitate is dried and then calcined at 400°C to 500°C for about 5 hours.
[0081] The exhaust gas purification catalyst comprising the monolith substrate of the present invention has a structure in which precious metal particles are supported on the monolith substrate of the present invention. The precious metal particles are preferably one or more metals selected from platinum group metals, particularly Pt, Rh and Pd. The content of the precious metal particles is not limited, but is usually 0.1 g to 2.0 g, preferably 0.3 g to 1.5 g, for each metal per 1 L of the exhaust gas purification catalyst. The precious metal particles may be supported on the monolith substrate by mixing with a co-catalyst (oxygen storage material), a carrier, a binder, etc. to prepare a slurry, and then wash-coating the monolith substrate with the slurry, as in the past. However, since the monolith substrate of the present invention itself has the functions of a co-catalyst and a carrier, high purification performance can be expected even if the precious metal particles are directly supported. In particular, since the low heat capacity of the three-way catalyst is effective in reducing Cold-HC, the catalyst can be made to have a low heat capacity by eliminating the wash coat, and higher HC purification performance can be expected. The noble metal can be supported using common reagents such as palladium nitrate and rhodium chloride.
[0082] The exhaust gas purification catalyst of the present invention has a higher stoichiometric retention ability and higher exhaust gas purification performance, especially HC purification performance, because the monolith substrate contained in the exhaust gas purification catalyst quickly absorbs and releases oxygen to keep the oxygen concentration constant, even under conditions in which the air-fuel ratio fluctuates, particularly under conditions in which the air-fuel ratio fluctuates within a small range, for example, under conditions in which the air-fuel ratio fluctuates between 14.6±0.2 (14.4 and 14.8). EXAMPLES
[0083] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0084] 1. Preparation of Three-way Catalyst Using Al2O3-CeO2-ZrO2 composite oxide particles (ACZ) and CeO2-ZrO2 composite oxide particles (CZ) having the compositions shown in Table 1, exhaust gas purification catalysts of Comparative Examples 1 to 3 and Example 1 were produced according to the specifications shown in Table 2.
[0085] The exhaust gas purification catalysts of Comparative Examples 1 to 3 were prepared using a monolith substrate manufactured by firing Al2O3-CeO2-ZrO2 composite oxide particles, CeO2-ZrO2 composite oxide particles, Al2O3 particles, boehmite as an Al2O3 binder, and Al2O3 fibers at 1150°C. Since this monolith substrate is considered to have a precious metal particle (catalyst) carrier function and a co-catalyst function, a predetermined amount of precious metal was directly supported on the substrate without washcoating. Specifically, the substrate was immersed in an aqueous solution in which a required amount of palladium nitrate and rhodium chloride were dispersed, and left for a certain period of time to support the precious metal on the substrate. The substrate capacity of the exhaust gas purification catalysts of Comparative Examples 1 to 3 was 0.9 L.
[0086] The exhaust gas purification catalyst of Example 1 was prepared using a monolith substrate manufactured by firing Al2O3-CeO2-ZrO2 composite oxide particles, Al2O3 particles, boehmite as an Al2O3 binder, and Al2O3 fiber at 1150°C. Since this monolith substrate is considered to have a catalyst carrier function and a co-catalyst function by itself, a predetermined amount of precious metal was directly supported on the substrate without washcoating. Specifically, the substrate was immersed in an aqueous solution in which a required amount of palladium nitrate and rhodium chloride were dispersed, and left for a certain period of time to support the precious metal on the substrate. The substrate capacity of the exhaust gas purification catalyst of Example 1 was 0.9 L in each case.
[0087] [Table 1]
[0088] [Table 2]
[0089] 2. Measurement of pore volume of 0.03μm or less The pore volumes of 0.03 μm or less of the monolith substrates of Example 1 and Comparative Examples 1 to 3 were measured by mercury intrusion porosimetry in accordance with JISR1655:2003. Specifically, a cube with a side length of about 0.8 cm was cut out from the monolith substrate as a measurement sample, which was then ultrasonically cleaned with ion-exchanged water and thoroughly dried. Subsequently, the pore volumes of the measurement samples were measured by an automatic porosimeter Autopore III9405 (manufactured by Micromeritics). The measurement range was the pore volume of pores with diameters in the range of 0.006 μm to 500 μm, the pore volume of pores with diameters in the range of 100 μm to 500 μm was measured at pressures of 0.1 psia, and the pore volume of pores with diameters in the range of 0.006 μm to 100 μm was measured at pressures of 0.25 psia. At that time, the contact angle was set to 130° and the surface tension was set to 485 mN / m. From the obtained pore volume results for pores with diameters in the range of 0.006 μm to 500 μm, the pore volume for pores with diameters of 0.03 μm or less was determined.
[0090] 3.Low temperature activity evaluation The exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3 were installed in an in-line 4-cylinder 2.5L engine, and the temperature was gradually increased from a low temperature to measure the temperature of the exhaust gas purification catalyst at which the HC purification rate became 10% (low-temperature activity temperature). The low-temperature activity temperature of each exhaust gas purification catalyst was compared with the low-temperature activity temperature of a reference catalyst (a commonly used exhaust gas purification catalyst in which a catalyst coating layer is formed on the wall surface of a honeycomb-shaped cordierite monolith substrate), and the difference was taken as the low-temperature activity (°C) (HC-T10).
[0091] 4. Evaluation Results Table 3 shows the results of the pore volume of pores of 0.03 μm or less and the low-temperature activity of the exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3.
[0092] [Table 3]
[0093] FIG. 1 shows the relationship between the ACZ ratio {[(ACZ (wt%)) / (ACZ (wt%) + CZ (wt%) + Al2O3 (wt%) + binder fiber (wt%))] × 100} and the pore volume of 0.03 μm or less for the exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3. From Table 3 and FIG. 1, when comparing the exhaust gas purification catalyst of Example 1 with the exhaust gas purification catalysts of Comparative Examples 2 and 3, it was found that the exhaust gas purification catalyst of Example 1 has a larger pore volume of 0.03 μm or less. This is because the exhaust gas purification catalyst of Example 1 has a higher ratio of ACZ, which is more heat resistant than CZ, compared to the exhaust gas purification catalysts of Comparative Examples 2 and 3. In addition, when comparing the exhaust gas purification catalyst of Comparative Example 1 and the exhaust gas purification catalyst of Comparative Example 3, which have almost the same ratio of ACZ, it was found that the exhaust gas purification catalyst of Comparative Example 1 has a smaller pore volume of 0.03 μm or less. This is because, compared to the exhaust gas purification catalyst of Comparative Example 3, the exhaust gas purification catalyst of Comparative Example 1 has a lower ratio of Al2O3, which has the highest heat resistance among ACZ, CZ, and Al2O3.
[0094] Fig. 2 shows the relationship between the pore volume of 0.03 μm or less and the low-temperature activity HC-T10 of the exhaust gas purification catalysts of Example 1 and Comparative Examples 1 to 3. From Table 3 and Fig. 2, it was found that the low-temperature activity improves as the pore volume of 0.03 μm or less of the exhaust gas purification catalyst increases. In particular, it was found that the low-temperature activity of the exhaust gas purification catalyst is superior to that of the reference catalyst when the pore volume of 0.03 μm or less is 0.20 ml / g or more.
Claims
1. A honeycomb-shaped monolith substrate containing a ceria component, The monolith substrate has a pore volume of 0.03 μm or less of 0.20 ml / g or more; The content of the ceria component is 6% by weight or more and less than 13% by weight based on the total weight of the monolith substrate; the monolith substrate contains an alumina-ceria-zirconia composite oxide as a ceria component; The content of the alumina-ceria-zirconia composite oxide is 40% by weight to 60% by weight based on the total weight of the monolith substrate; the monolith substrate further comprises particles of alumina; The content of alumina particles is 28% by weight to 32% by weight based on the total weight of the monolith substrate; Monolith substrate.
2. An exhaust gas purification catalyst comprising the monolith substrate according to claim 1 and precious metal particles.
Citation Information
Patent Citations
Exhaust gas treatment catalyst and production method of the same
JP2003170043A
Catalyst body
JP2003236381A
Ceramic catalyst
JP2004066069A
Catalyst carrier for exhaust gas purification, catalyst for exhaust gas purification using the same, production method of catalyst carrier for exhaust gas purification
JP2014000552A
Exhaust gas purification catalyst
JP2015085241A